Digital-Based Marketing Strategy Innovation ForImproving Company Competitiveness - Farhan Achmad Fajari (Journal of Strategic Innovation in Economics and Business, 2025)
Digital transformation has encouraged companies to adopt innovative digital-based marketing strategies to increase competitiveness in an increasingly competitive business era. This research examines the role of innovation in digital marketing strategies, such as search engine optimization (SEO), social media marketing, and data analytics. A literature review approach is used to identify key elements of an effective marketing strategy. The research results show that digital technology can expand market reach, increase operational efficiency, and create a personalized customer experience. These findings underscore the importance of continuous innovation and technological adaptation to address market changes. Thus, this research provides practical guidance for companies to design relevant and competitive digital marketing strategies.